Distribution of Zooplankton in the South of Al-Hammar Marshes, Southern Iraq - Abbas, Mohammed F.; Ajeel, Shaker G. (Mesopotamian Journal of Marine Sciences, 2022)
Seasonal variation of the quality and quantity of zooplankton was studied in four selected stations of Southern Al-Hammar Marshes, from October 2018 to July 2019. Plankton net (0.1 mm. mesh size) was used to collect the samples of zooplankton. The population density of zooplankton in the study area ranged from 725 ind./m3 in Summer 2019 at station 1 (Al-Barga station) to 151413 ind./m3 in Autumn 2018 at station 3 (Hareer station), with an average of 39336 ind./m3. The Crustacea was the dominant group; it was accounted for (96.3%) of the total zooplankton, Copepoda constituted about (80.3%) followed by Cirripede larvae (13%), Rotifera (3.3%), and Cladocera (2.4%) of the total zooplankton. The Cyclopoida was the dominant group of Copepoda at all stations (95.6%), followed by the nauplii of Copepoda (2.8 %), Calanoida (1.3 %) and Harpacticoida (0.3 %).